1975
DOI: 10.1161/01.res.37.5.558
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of acute renal failure following temporary renal ischemia in the rat.

Abstract: In this study, we characterized the sequence of several intrarenal events and evaluated their relative importance in the pathogenesis of unilateral oliguric acute renal failure induced experimentally in rats by complete occlusion of a renal artery for 1 hour. Kidneys were studied prior to occlusion and 1-3 hours and 22-26 hours after release of the temporary occlusion. Renal blood flow measured by an electromagnetic flow transducer was reduced to 40-50% of control during both postocclusion periods. Flow of tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
2
6

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(104 citation statements)
references
References 14 publications
10
86
2
6
Order By: Relevance
“…Reperfusion after ischemic injury results in a partial recovery of renal blood flow, with a reduction in renal blood flow of up to 50% after reperfusion (33). This persistent reduction in total and regional renal blood flow (34-36) was described several decades ago as the Figure 1.…”
Section: The No-reflow Phenomenon Jeopardizes Renal O 2 Supplymentioning
confidence: 93%
“…Reperfusion after ischemic injury results in a partial recovery of renal blood flow, with a reduction in renal blood flow of up to 50% after reperfusion (33). This persistent reduction in total and regional renal blood flow (34-36) was described several decades ago as the Figure 1.…”
Section: The No-reflow Phenomenon Jeopardizes Renal O 2 Supplymentioning
confidence: 93%
“…Pathophysiological mechanisms involved in the decline in GFR can be attributed to persistent vasoconstriction due to an imbalance between vasoconstrictive and vasodilatory mediators (36,37); vascular obstruction caused by endothelial-leukocyte interactions (31,187); tubuloglomerular feedback in response to increased solute delivery to the macula densa (104,142); tubular obstruction caused by detachment of tubular epithelial cells from the basement membrane and back-leak of glomerular filtrate as a consequence of disruption of the epithelial cell layer (5,20,21,65).…”
Section: Cell Death In Ischemic Acute Renal Failurementioning
confidence: 99%
“…Even with severe ischemia, tubular obstruction was observed early, but a day after IR, marked preglomerular vasoconstriction, presumably caused by tubuloglomerular feedback activation, was prominent. 18 Peterson et al 19 also observed a direct role for tubuloglomerular feedback, where intratubular administration of uranyl nitrate immediately reduced SNGFR. With no systemic exposure to the nephrotoxin, only a local tubuloglomerular feedback mechanism could explain the immediate decline in SNGFR, and with tubuloglomerular feedback inhibition, SNGFR was preserved.…”
Section: Discussionmentioning
confidence: 97%